La otredad existencial en la cuentística de Julio Ramón Ribeyro - Espinoza Aguilar, Ronald Antenor (2019)
The criticism influenced by marxist philosophy, as well as criticism influenced by other philosophical tendencies, have directed the study of short ribeyrian narrative towards aspects such as marginality and skepticism. It could be said that a work, apparently, simple and simple, like Ribeyro’s short narrative, actually contains a complex fictional universe that can not be tackled unilaterally from a single glance, since that would only lead us to see in the ribeyrian characters traces and copies of exploited social classes or grotesque and deluded beings within an unjust social system. In disagreement with the previous perspectives, we propose that, although the problem of mimesis is deeply rooted in the ribeyrian storybook and becomes visible at a distance, it is not mainly social problems or cognitive problems that truly anguish his characters, but the existential problems.